Uji Kesesuaian Kolimasi pada Modalitas Digital Radiography dalam Menilai Luas Penyinaran - Mirfauddin, Mirfauddin; Satrio, Revan; Darmawan, Zulkifli Tri; Pradana, Alfa (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
The X-ray collimator is an essential device in digital radiography to ensure the accuracy of radiation field size, image quality, and patient safety. This study aimed to evaluate the collimation conformity of digital radiography equipment at the Radiology Installation of Pelamonia Hospital Makassar in determining the accuracy of radiation field size. A descriptive quantitative method was used with a collimator test tool measuring 18 × 14 cm and a source-to-image distance (SID) of 100 cm. The tests were conducted three times through direct exposure, measuring the deviation between collimator light and X-ray field. The first test showed horizontal deviation of 0.2% and vertical deviation of 0.1%. The second test recorded horizontal deviation of 0.2% and vertical deviation of 0.1%. The third test also showed horizontal deviation of 0.2% and vertical deviation of 0.1%. All results were within the tolerance limits, with individual axis deviations of ≤2% and combined total deviation of ≤3% according to national standards. In conclusion, the digital radiography equipment at Pelamonia Hospital Makassar met safety standards and is suitable for clinical use to support patient safety and optimal image quality.